Catalysis and regioselectivity in hydrofunctionalization reactions of unsaturated carbon bonds. Part II. Hydroamination. (31st October 2020) - Beletskaya, I P; Nájera, C; Yus, M
Abstract: This review continues consideration of the regioselectivity problem in the catalyzed hydrofunctionalization of unsaturated organic compounds and addresses hydroamination of unsaturated hydrocarbons. Particular parts of the review deal with reactions of alkenes, alkynes, allenes and dienes. It is shown that the selectivity of hydroamination depends on the natures of the reactants and the catalyst. Conditions of the reactions are described; in some cases, reaction mechanisms are discussed. Reactions for which divergent regioselectivity is possible are noted. The bibliography includes 250 references.